Nagle poczuli się wolni. Z Piotrem Bojarskim rozmawia Jerzy Borowczyk - Bojarski, Piotr; Borowczyk, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
An interview with Piotr Bojarski, author of historical non-fiction and novels about Poznań 1956 protests, focusing on a few topics. The attitudes and fortunes of doctors, paramedics, security officers, heroic protesters of the Black Thursday, lawyers who defended the protesters – all this allows us to look at a single day in Polish history through a few prisms. Additionally, the interview contains remarks on the benefits of a reporter’s look at history, and the attempts at novelistic emplotment of the events of 1956.